An Evaluation Tool for National‐Level Pandemic Influenza Planning. Issue 2 (13th June 2019) - McKay, Stephanie; Boyce, Matthew; Chu‐Shin, Shieh; Tsai, Feng‐Jen; Katz, Rebecca
Abstract : The historical threat of pandemic influenza and the circulation of novel influenza viruses have led countries to strengthen their efforts in pandemic influenza preparedness planning. A cornerstone of these efforts is the creation of a comprehensive national plan that addresses all of the capacities required to prevent, detect, and respond to novel influenza outbreaks. In 2017 and 2018, the World Health Organization issued updated guidance for national pandemic planning efforts, based on lessons learned from the 2009 influenza A (H1N1) outbreak, the International Health Regulations (World Health Organization, 2005a), and other developments in health security. We have created a tool to assess national‐level plans based on these updated guidelines. This tool will allow for countries to identify both strengths and weaknesses in their national plans, identify capacities and sectors that require improvement, and to help frame the updating or drafting of plans in line with the most updated guidance.